2020
DOI: 10.14198/jhse.2022.173.09
|View full text |Cite
|
Sign up to set email alerts
|

Temporo-spatial gait adaptations while walking on different surfaces in Latino-Hispanic adults with controlled type II diabetes

Abstract: Those with Type 2 Diabetes with and without peripheral neuropathy (PN) display evident gait deficiencies, and kinematic alterations while stepping on various surfaces. Purpose: To verify if such modifications would emerge performing diverse tasks in the regulated stages of diabetes such as controlled type 2 diabetics without PN. Methods: We recruited and allocated 30 adult participants in two groups, 15 controlled diabetics (cDMII) and 15 controls (CoG). Gait temporospatial criteria were measured during even w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…However, increased deviations in distance and sway seen in the CT2DM participants is concerning, as this could potentially foreshadow both the sustaining of alterations to sensory systems and becoming fall risks in the future. Several researchers now contend that, even prior to the presence of peripheral neuropathy, diabetic patients can exhibit balance and gait impairments [18,35] with increased joint movements, decreased gait speed, decreased cadence, reduce single limb support during gait, increased sway as well as heightened abnormalities in those who present with neuropathy [8,14,36]. We believe that balance variations were insignificant in our study due to the static balance conditions in the protocol not being strenuous enough to prescribe balance difficulties in our participants.…”
Section: Bbsmentioning
confidence: 73%
See 1 more Smart Citation
“…However, increased deviations in distance and sway seen in the CT2DM participants is concerning, as this could potentially foreshadow both the sustaining of alterations to sensory systems and becoming fall risks in the future. Several researchers now contend that, even prior to the presence of peripheral neuropathy, diabetic patients can exhibit balance and gait impairments [18,35] with increased joint movements, decreased gait speed, decreased cadence, reduce single limb support during gait, increased sway as well as heightened abnormalities in those who present with neuropathy [8,14,36]. We believe that balance variations were insignificant in our study due to the static balance conditions in the protocol not being strenuous enough to prescribe balance difficulties in our participants.…”
Section: Bbsmentioning
confidence: 73%
“…Diabetes and diabetes-related PN impact multiple areas that ultimately jeopardize patients' functionality and autonomy [15,16] by disturbing their balance [17] and gait [12]. Inquiries have previously established that upon being compared to healthy control groups, diabetes in the initial or controlled stages of the disease can show early manifestations of altered morphology and movement patterns [18,19]; however, some underlying variations might not be as easily detectable in those who are in the early stages of T2DM. Thus, there is a clear justification for further investigations to examine whether outcome measures alone can differentiate activity performances in patients with controlled T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it showed impairment in the dynamic gait index, with an average of 19 +/± 5.45%, correlating with an increased fall risk. We consider the TA was recruited further to ensure toe clearance from the treadmill surface as the incline increased (Rosario et al, 2018(Rosario et al, , 2020. This prolonged activation can boost the endurance capabilities of said muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The opposite direction of these variables is indicative of dynamic balance issues. Rosario et al, (2022) identified few gait variables affected in individuals with controlled diabetes compared with age-and weightmatched non-diabetics [22]. One of these variables was a reduction in SLS time, which the authors pointed out to be of clinical importance as a predictor tool.…”
Section: Discussionmentioning
confidence: 99%